Partisipasi Mahasiswa KKN UNP dalam Membantu Proses Belajar Mengajar di SDN 08 Nagari Indudur - Leni Zahara; Indah Maharani Fortuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educational resource limitations in remote areas pose a crucial challenge to equitable education quality in Indonesia. This research examines the vital role of